The lionkeeper of Algiers : the extraordinary life of James Leander Cathcart from Barbary pirate hostage to American diplomat in the eighteenth century /: the extraordinary life of James Leander Cathcart from Barbary pirate hostage to American diplomat in the eighteenth century. (2023) - Ekin, Des
No abstract available